FAKTOR PENYEBAB KECENDERUNGAN KENAKALAN REMAJA DAN ALTERNATIF BK YANG DAPAT DIBERIKAN PADA SISWA KELAS XI - Sianipar, Ary Franswendo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This thesis entitled "Causes of Juvenile Delinquency Trends and BK Alternative to Cast On Grade X1 SMK Mandiri Pontianak". A common problem in this research is "What are the factors of juvenile delinquency trends and alternatives BK can be given in class XI SMK Mandiri Pontianak. Sub question: What are the forms of juvenile delinquency and alternative BK that can be given in class XI SMK Mandiri Pontianak? What are the psychological factors causing juvenile delinquency trends and BK alternatives that can be provided in class XI SMK Mandiri Pontianak What are the physiological factors causing juvenile delinquency trends and BK alternatives that can be provided in class XI SMK Mandiri Pontianak What are the sociological factors causing juvenile delinquency trends and BK alternatives that can be provided in class XI SMK Mandiri PontianakThe research variables are factors causing juvenile delinquency trends and alternatives that can be given BK method used is descriptive method with quantitative approach to shape analysis. The population of this research consisted of 84 class XI SMK Mandiri Pontianak. Data collection techniques in this study is the indirect techniques. Data collection tool was a questionnaire. Based on the results of data analysis of the factors causing juvenile delinquency trends in class XI student of SMK Mandiri Pontianak totaled 84% in the category Good enough. Â  Keywords: Causes, Trends, Juvenile Delinquency